Stimulus Equivalence and Increase of Correct Responses in Addition and Subtraction Problems - Henklain, Marcelo Henrique Oliveira; Carmo, Joao dos Santos (Paidéia (Ribeirão Preto), 2013)
In order to propose interventions that increase correct responses, investigations search for properties of arithmetic problems that hinder its solution. This study assessed whether the formation of two sets of addition and subtraction equivalence classes reaches that goal. It also investigated the effect of training in balance-type problem solving and the teaching of algorithms. Eight second to fifth-grade elementary school students served as participants. After the formation of classes, all participants showed an average growth of 25% at post-test 1. Later, at the end of the training in balance-type problem solving, there was an average growth of 25% in post-test 2. In Generalization Test 1, all participants showed correct responses above 75%. After the teaching of algorithms, an average growth of 8% was detected in Post-test 3, and 100% correct answers in the reapplication of the test generalization. The procedures employed produced gains in solving arithmetic problems behavior.